Physical Fitness of Female Soccer Players Based on Playing Position - Dzihan Khilmi Ayu Firdausi; Muhammad Eka Mardyansyah Simbolon (Universitas Pendidikan Indonesia, 2021)
The purpose of this study was to gain insight into female soccer players’ physical performance profiles by observing their position in the field. The sample consisted of 17 athletes who were involved in regional training at the Papua National Sports Week (PON) 2021. The players were divided into three subgroups based on their position, including specific strikers, midfielders, and backs. The samples performed 10 item tests measuring physical performance components. Based on the playing position, there was no difference of BMI among the strikers, midfielders, and backs (F = 0.174, p 0.05). The results of the bleep test showed no difference (F = 0.466, p 0.05). The results of leg dynamometer (F = 0.898, p 0.05), back dynamometer (F = 1.350, p 0.05), and sit and reach (F = 0.543, p 0.05) also showed no difference. There was also no difference in measurement results of hand dynamometer pull (F = 0.028, p 0.05) and push (F = 1.107, p 0.05). Moreover, the result of 50-meter sprint (F = 0.404, p 0.05), sit up (F = 0.493, p 0.05), push up (F = 2.204, p 0.05), and shuttle run (F = 0.991, p 0.05) also showed no difference. We believe that a female football player athletic ability is unaffected by their position in the field. The absence of variation in physical ability observed among female soccer players may be attributed to BMI. Coaches may use these results as reference data to classify strengths, select players, and monitor the preparation.